The store ebook - Patterson, James (2017)
When Jacob and Megan Brandeis plan to expose a secretive and evil corporation, the fallout threatens to destroy them. Jacob and Megan Brandeis have gotten jobs with the mega-successful, ultra-secretive Store. Seems perfect. Seems safe. But their lives are about to become anything but perfect, anything but safe. Especially since Jacob and Megan have a dark secret of their own. They're writing a book that will expose the Store-a forbidden book, a dangerous book. And if the Store finds out, there's only one thing Jacob, Megan and their kids can do: run for their bloody lives. Which is probably impossible, because the Store is always watching . . .